Care sought and normative need assessment for dental caries among rural adults in jeelugumelli mandal, Andhra Pradesh, India - Chinna Babu Palli; Srinivas Pachava; Parveen Sultana Shaik; Srinivas Ravoori; Suresh Chand Yaddanapalli; Asha Lodagala (Wolters Kluwer Medknow Publications, 2022)
Introduction: Different rates of dental caries prevalence are experienced among different populations due to the influence of various demographic, political, and socioeconomic factors. Aim: To assess the prevalence of dental caries, the type of self-care remedies utilized, and normative needs assessment among rural adults residing in Jeelugumelli Mandal, West Godavari District, Andhra Pradesh, India. Materials and Methods: A cross-sectional survey was conducted among 800 adults by using a multi-stage random sampling technique in Jeelugumelli Mandal, West Godavari District, India. Data were collected using a pretested pro forma consisting of questionnaire-related demographics, traditional care, and clinical examination which was investigated by a single examiner to record caries experience (Decayed, Missing, and Filled Teeth [DMFT]) using WHO 1997 criteria. The data were analyzed using IBM SPSS Statistics, Version 20.0. Mann-Whitney U-test, Kruskal-Wallis, and Multivariate Linear Regression analysis tests were used and the level of significance was set at P ≤ 0.05. Results: Mean DMFT value of the study population was 10.29 ± 4.806 and 33.4% of the subjects had used home remedies related to plant origin. The majority of the study population required surgical need (Extractions) with a mean value of 4.23 ± 5.553 and compared with unskilled workers, unemployed workers had 2.8 units higher chances of having caries (R = 2.810 confidence interval [CI] 1.876-3.744) while it was 5.031 units lesser for professionals in having caries (R = −5.031 CI [−4.16] - [−5.901]). Conclusion: Dental caries prevalence and normative needs for dental caries were high in the adult population residing in Jeelugumelli Mandal and most of the individuals are depending on self-care procedures to relieve pain.